Paediatric ED reattendance rates: comparing nurse practitioners and other clinicians. Issue 5 (5th June 2014) - Feetham, Jane E; Christian, Will; Benger, Jonathan R; Hoskins, Rebecca; Odd, David; Lyttle, Mark D
Abstract : Objective: The aim of this project is to establish the unplanned reattendance rate for paediatric emergency nurse practitioners (PENPs) working in a designated paediatric emergency department (PED) while identifying the case mix of patients seen by PENPs compared with their medical counterparts. Design: Quantitative data regarding patient characteristics and reattendance were collected during retrospective review of case notes across two representative 2-week periods. Setting: The study site is a tertiary urban PED with an annual attendance of 32 000 patients aged from birth to 15 years. Main outcome measures: Reattendance rates, patient characteristics, triage scores, presenting complaint and numbers of patients discussed with a paediatric emergency medicine consultant were evaluated. Results: The results showed that PENPs have a lower reattendance rate (1.75%) when compared with senior and junior doctors in training (4.29%, 5.76%); however, PENPs treat a different population of children. When the odds of PENP reattendance are adjusted for this, the significance of the difference becomes less certain. Conclusions: PENPs work autonomously when seeing children presenting with minor trauma and make a positive contribution in achieving the reattendance Clinical Quality Indicator.